Low Molecular Weight Hydrogel for Wound Healing - Shangyan Gu; Yu Lu; Yuji Wang; Wensheng Lu; Wei Wang (MDPI AG, 2023)
Octadecylazanediyl dipropionic acid (C18ADPA) is a zwitterionic amphiphile with a dendritic headgroup. C18ADPA self-assembles to lamellar networks, which encompasses water and forms a low-molecular-weight hydrogel (LMWG). In this study, we use the C18ADPA hydrogel as a drug carrier for the in vivo delivery of a copper salt for wound healing in a mouse model. A structural transition was observed based on cryo-scanning electron microscope (cryo-SEM) images after drug loading. The C18ADPA hydrogel, which had a layered structure, transformed into a self-assembled fibrillar network (SAFiN). The mechanical strength of the LMWG has always been an important issue in its applications. However, due to the structural transition, both the storage and loss moduli increased. In vivo tests showed that wound closure was faster after applying the hydrogel formulation compared with the Vaseline formulation. For the first time, we have also provided histological evidence of these effects on skin tissue. The hydrogel formulation exhibited clear advantages in regenerating tissue structure over traditional delivery formulations.